Diversidad y similitudes faunísticas de los bivalvos de las Islas del Arco de Scotia - Zelaya, Diego Gabriel (2005)
Species richness of the shallow-water bivalves from the Scotia Arc islands was studied on the basis of new collections and by reviewing extant information. Seventy-three species are recognised from the entire area. South Georgia, the South Orkney Islands and the South Shetland Islands were similar in species richness to the Antarctic Weddell sector. New records for 51 bivalve species are provided and the presence of 18 undescribed species is reported. The faunistic similarity of the islands of the Scotia Arc to the Magellan region and the Antarctic Weddell sector is re-examined. These islands show a high similarity to the Antarctic Weddell sector (49 to 85%) and a low similarity to the Magellan region (12 to 32%). Evidence from bivalves clearly supports the placement of the Scotia Arc islands within the Antarctic region.